Correlational Analysis of the Availability and Usage of Geographic Information Systems by Students and Lecturers an Higher Educational Institutions - Osakwe, Jude Odiakaosa; Ankome, Teresia; Ujakpa, Martin (Asosiasi Doktor Sistem Informasi Indonesia, 2021)
There has been a rapid development of Information and communication Technologies (ICTs) globally, and this includes the Geographic Information Systems (GISs) which has evolved over the years and aimed at solving many geographic problems as fast and efficiently as possible. The importance of GIS to students and lecturers in higher educational institutions is it’s ability to easily analyse locations together with the conventional database systems. This paper assessed the correlation between the availability and use of GIS in Higher Educational Institutions (HEIs). The study is exploratory in nature and employed the use of questionnaires as instrument to collect data. Simple random sampling technique was used to select one hundred and ten (110) lecturers one thousand five hundred and seventy-nine (1579) students from a university. Findings revealed that GIS for analysis is still at its lowest ebb and hence calls for an action to motivate or encourage lecturers and students to use it. Though there are indications that GIS will be of great value in schools, students and lecturers they will be happy to use it for their teaching and learning. The study also revealed availability of GIS was not tied to its usage.